Bevacizumab+chemotherapy versus chemotherapy alone in elderly patients with untreated metastatic colorectal cancer: a randomized phase II trial—PRODIGE 20 study results. (28th September 2017) - Aparicio, T; Bouché, O; Taieb, J; Maillard, E; Kirscher, S; Etienne, P -L; Faroux, R; Khemissa Akouz, F; El Hajbi, F; Locher, C; Rinaldi, Y; Lecomte, T; et al.
Abstract: Background: Metastatic colorectal cancer frequently occurs in elderly patients. Bevacizumab in combination with front line chemotherapy (CT) is a standard treatment but some concern raised about tolerance of bevacizumab for these patients. The purpose of PRODIGE 20 was to evaluate tolerance and efficacy of bevacizumab according to specific end points in this population. Patients and methods: Patients aged 75 years and over were randomly assigned to bevacizumab + CT (BEV) versus CT. LV5FU2, FOLFOX and FOLFIRI regimen were prescribed according to investigator's choice. The composite co-primary end point, assessed 4 months after randomization, was based on efficacy (tumor control and absence of decrease of the Spitzer QoL index) and safety (absence of severe cardiovascular toxicities and unexpected hospitalization). For each arm, the treatment will be consider as inefficient if 20% or less of the patients met the efficacy criteria and not safe if 40% or less met the safety criteria. Results: About 102 patients were randomized (51 BEV and 51 CT), median age was 80 years (range 75–91). Primary end point was met for efficacy in 50% and 58% and for safety in 61% and 71% of patients in BEV and CT, respectively. Median progression-free survival was 9.7 months in BEV and 7.8 months in CT. Median overall survival was 21.7 months in BEV and 19.8 months in CT. The 36-month overall survival rate was 27% in BEV and 10.1% in CT. Severe toxicities grade 3/4 were mainly non-hematologic toxicities (80.4% in BEV, 63.3% in CT). Conclusion: Bevacizumab combined with CT was safe and efficient. Both arms met the primary safety and efficacy criteria.